Sustainability principles and practice - Robertson, Margaret (2021)
"This new and expanded edition builds upon the accessible and comprehensive overview of the interdisciplinary field of sustainability. The focus is on furnishing solutions and equipping the student with both conceptual understanding and technical skills for the workplace. Each chapter explores one aspect of the field, first introducing concepts and presenting issues, then supplying tools for working toward solutions. Techniques for management and measurement as well as case studies from around the world are provided. The third edition includes a complete update of the text, with increased visual material and pedagogy to guide students in their learning. Chapters include further reading and discussion questions. The book is supported by a companion website with links, detailed reading lists, glossary, and additional case studies, together with projects, research problems, and group activities, all of which focus on real-world problem solving of sustainability issues. The textbook is designed to be used by undergraduate college and university students in sustainability degree programs and other programs in which sustainability is taught"--
Revised edition of the author's Sustainability principles and practice, 2017.
Includes bibliographical references and index.
Keywords: Sustainability; Sustainable development; Environmental economics